Persepsi Akseptor KB Tentang Pemakaian Metode Kontrasepsi Jangka Panjang di Puskesmas Koni Kota Jambi - Arifarahmi Arifarahmi (Jurnal Ilmiah Universitas Batanghari Jambi, 2018)
Indonesia is the nation with the third largest population in the world. One way to control the population is with the family planning program. The strategy of the implementation of KB program is increase the use of long-term contraceptive methods (MKJP) sterilization (MOW and MOP), IUD and implant. The research used descriptive research; it aimed to determine perception of acceptor KB about use of long-term contraceptive methods at the public health center Koni Jambi city year 2017. Populations were 1.686 people. It used accidental sampling technique i.e. acceptor KB who visit the public health center. Sample for this research was 42 womens. Analyzed univariate was used for statistical analysis. The collecting data used by questionnaire. The result showed 9 acceptors (21%) used MKJP and 33 acceptors (79%) choose to use contraceptive non MKJP. 29 acceptors (69%) have positive perception and 13 acceptors (31%) have negative perception about use of long-term contraceptive methods. It concluded that there are many acceptor more choose and use contraception non MKJP, it suggested to increase promotion in conducting counseling about contraception to increase awareness of acceptor for themselves especially MKJP contraceptives.